La cartographie d’une sélection globale de flux, entre ‘significativité’ et ‘densité’ - Françoise Bahoken (Netcom)
One of the main responses for reducing the cartographic complexity of a flow (or a movements) map is to select the information with “parsimony”. If several approaches remain available, one of them is to mobilize a single criterion (α), endogenous to the matrix. We present here the implementation of such unique selection criteria that we called “global criteria”. From a solution initially proposed by Tobler (1982), we analyze the flow values (Fij) statistical distribution by mobilizing graphical tools. That leads us to propose a (double) single criterion so as to represent only these flow values responding to a significance or a density matrix objective. The empiric validation is made on a French commuters flow matrix.